Awards: International Virtual Educational Invention, Innovation and Design Competition (iVEDIIC2020) and The Virtual National e-Content Development Competition 2020 - UiTM, Fakulti Sains Gunaan (Faculty of Applied Sciences, 2020)
The Faculty of Applied Sciences (FSG), Universiti Teknologi MARA (UiTM), has received prestigious recognition in both international and national competitions for educational innovation. Congratulations to Ts. Dr. Judith Gisip, Cik Azrena Abdul Karim and Dr. Imelda Albert Gisip for winning silver at International Virtual Educational Invention, Innovation and Design Competition (iVEDIIC2020) and to all winners for The Virtual National e-Content Development Competition 2020.